Rationality in Digital Da‘wah: Reconstructing Islamic Religious Education Through Social Media - Rifky Gimnastiar; Ansori; Muhammad Nazim Adil (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
The rapid development of digital technology has transformed social media into an influential platform for communication, knowledge dissemination, and religious learning. In the context of Islamic Religious Education (IRE), social media has increasingly functioned as an alternative learning resource that enables Islamic teachings to be delivered in more interactive, flexible, and accessible forms. This study aims to examine the role of social media as a learning resource for Islamic Religious Education, particularly in relation to educational innovation and value distortion within digital religious content. This research employed a qualitative descriptive approach using netnography and content analysis. The primary data source was the YouTube content Belajar Islam Pake Logika featuring Ustaz Felix Siauw on Raymond Chin’s channel, supported by audience comments, digital interactions, and relevant scholarly literature. The findings indicate that social media contributes significantly to the transformation of Islamic learning through rational communication, audiovisual interaction, and participatory learning environments that align with the characteristics of digital-native generations. Rational approaches in digital da‘wah encourage critical thinking, accessibility, and contextual understanding of Islamic teachings. However, the study also reveals significant challenges, including misinformation, oversimplification of religious teachings, pseudo-religious authority, and the commodification of religion driven by algorithmic visibility and popularity. These conditions may contribute to value distortion and fragmented religious understanding among audiences. Therefore, strengthening digital religious literacy is essential to ensure critical and responsible engagement with online religious content. The novelty of this study lies in its focus on rational digital da‘wah as both an innovative pedagogical strategy and a site of value contestation within social media environments.